Neural correlates of verb and noun processing: An fMRI study of Persian. (February 2016) - Momenian, Mohammad; Nilipour, Reza; Samar, Reza Ghafar; Oghabian, Mohammad Ali; Cappa, Stefano
Abstract: The purpose of this fMRI study is to examine the neural substrata of verb and noun processing within a grammatical context in Persian, a language with a complex morphosyntactic structure. The main aim was to assess the possible impact of the morphosyntactic properties of Persian on the neural representations of different grammatical categories. To this end, 14 healthy native speakers of Persian were required to covertly complete sentences by generating verbs or nouns within a grammatical context, in response to each relevant drawing. Common regions were activated by both verbs and nouns in occipital cortex, temporal cortex, and cerebellum. In the direct comparisons, only verb processing revealed larger activation in middle temporal gyrus (bilaterally) and left fusiform gyrus. This study, as the first report on Persian, demonstrates that verbs and nouns are processed and represented to a great extent via common cortical regions with few activation differences, possibly reflecting the verb-specific morphosyntactic properties of the Persian language. Highlights: We compared the neural correlates of verb and noun generation in Persian. Common regions were activated by both verbs and nouns in temporal cortex, cerebellum and occipital cortex. Verb generation revealed greater activation in bilateral middle temporal gyrus and in left fusiform gyrus. Noun generation showed no greater activation than verb generation.